The impact of freezing and toasting on the glycaemic response of white bread - Burton, P; Lightowler, H J (European journal of clinical nutrition, 2008)
Objective: To investigate the impact of freezing and toasting on the glycaemic response of white bread. Subjects/methods: Ten healthy subjects (three male, seven female), aged 22–59 years, recruited from Oxford Brookes University and the local community. A homemade white bread and a commercial white bread were administered following four different storage and preparation conditions: (1) fresh; (2) frozen and defrosted; (3) toasted; (4) toasted following freezing and defrosting. They were administered randomized repeated measures design. Incremental blood glucose, peak glucose response, 2 h incremental area under the glucose response curve (IAUC). Results: The different storage and preparation conditions resulted in lower blood glucose IAUC values compared to both types of fresh white bread. In particular, compared to the fresh homemade bread (IAUC 259 mmol min/l), IAUC was significantly lower when the bread was frozen and defrosted (179 mmol min/l, P <0.05), toasted (193 mmol min/l, P <0.01) and toasted following freezing and defrosting (157 mmol min/l, P <0.01). Similarly, compared to the fresh commercial white bread (253 mmol min/l), IAUC was significantly lower when the bread was toasted (183 mmol min/l, P <0.01) and frozen, defrosted and toasted (187 mmol min/l, P <0.01). Conclusions: All three procedures investigated, freezing and defrosting, toasting from fresh and toasting following freezing and defrosting, favourably altered the glucose response of the breads. This is the first study known to the authors to show reductions in glycaemic response as a result of changes in storage conditions and the preparation of white bread before consumption. In addition, the study highlights a need to define and maintain storage conditions of white bread if used as a reference food in the determination of the glycaemic index of foods.